Prevalence of Dengue Virus Transovarial Transmission and DHF Incidence Rate in Grogol Sub-district of Sukoharjo District - Paul Sunardi; Hari Kusnanto; Tri Baskoro T. Satoto; Lutfan Lazuardi (Universitas Muhammadiyah Yogyakarta, 2018)
Environmental changes in physical, biological, and social aspects have enabled the occurrence of DHF cases in Sukoharjo. Such changes may affect virulence of dengue virus, shorten extrinsic periods and increase vector dengue capacity. This study aimed to determine the spread of dengue virus transovarial transmission and the incidence rate of DHF in Grogol Sub-district of Sukoharjo District. This observational analytic study used a cross-sectional approach conducted in 2016. The population was Ae. aegypti mosquitoes and DHF patients (based on laboratory diagnosis with serologic examination, i.e., IgG, IgM and/or NS1 indicating positive DHF). Data analysis used Chi-square, Multiple Linear Regression, and spatially weighted regression with GeoDa and SatScan. The study found virDEN-3 transovarial transmission in Grogol Sub-district of Sukoharjo District and the spread of virDEN-3 transovarial transmission following the high spread of Ovitrap Index. The DHF incidences (cases) tended to cluster at a radius of 100-200 m from a region found the positive virDEN-3 transovarial transmission. The statistical tests showed a relationship between the virDEN-3 transovarial transmission and the DHF incidence with a p-value of <0.05. Spatially, the incidence of DHF in this area followed a certain spatial distribution pattern, with a clustering of dengue cases centered on the coordinates of -7.588240 S, 110.809450 E with a radius of 2.00 km.